Livestock as a source of income in rural areas - SINGH, PARMATMA; TIWARI, C B (The Indian Journal of Animal Sciences, 2013)
The potential of livestock in generating income on farms was investigated. For this the livestockÂ owners of the villages Atta (south) and Atta (north) of Bareilly district were selected. Information on different livestock products such as milk and dung, and values of draught power and agricultural products were collected for these livestock households from July 1989 to June 1992. Livestock contributed about one-third of the lotal income from agriculture including livestock. The farmers with small holdings hild large number of livestock while those with large farm holdings possessed proportionately small number of livestock. The skewed distribution is mainly responsible for under-utili zation of the livestock resources. Marginal farmers were more benefited from livestock on per household basis from milk. and draught power, Large and medium farmers received more income from milk as they were endowed with better milch cows and buffaloes. The use of bullocks and he buffaloes for fann work was mainly confined to marginal, small and medium households. Large farmers often used mechanical power for farm work. The results suggested that livestock offers a promising scope. For better and balanced development of livestock enterprise for the benefit of landless, marginal and small households, livestock needs attention of policy makers, planners and central and state governments.